Pengaruh Metode Pengeringan terhadap Kerusakan B-Karoten Mi Ubikayu yang Diperkaya Tepung Labu Kuning - Ruslina Azhariati; Sri Anggrahini; Zuheid Noor (agriTECH, 2002)
Pumpkin flour has high β-carotene, therefore, can be added to the noodle to alleviate vitamin A deficiency. Deterioration of β-carotene may take place during drying, proper control of the process to minimize the deterioration is necessary. The objective of the research was to study the β-carotene deterioration during drying process of the noodle and the physico-chemical properties of the cassava noodle that was enriched by pumpkin flour. The enrichment of the cassava flour was made by adding pumpkin flour various proportions 0, 5, 10 and 15 %. Noodle was sun dried for 8 hours, in cabinet dryer at 60ºC for 3 hours and in a two step cabinet dryer (60ºC for 2 hours followed by drying at 55ºC for 2 hours. The result showed that sun drying cause the greatest deterioration of β-carotene (46.24%). However, enrichment of pumpkin flour can improved the color, protein and β-carotene content of the noodle.